A non-transition / transition metal synergistically enhanced and toughened high-entropy carbide ceramic material and a preparation method thereof
By combining non-transition metals with transition metals and ball milling and SPS technology, high-entropy carbide ceramics with high density, high hardness and high toughness were prepared. This solved the problems of high preparation temperature and high brittleness of high-entropy carbide ceramics, and achieved densification and toughening effects at lower temperatures.
Patent Information
- Application Number
- CN202610425787.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-02
- Publication Date
- 2026-08-25
AI Technical Summary
High-entropy carbide ceramics are prepared at extremely high temperatures and have low fracture toughness, making them prone to brittle fracture under mechanical impact or thermal shock. Furthermore, traditional metal binders have poor wettability in complex matrices, making it difficult to control the interfacial bonding strength, which can lead to pore residues or interfacial delamination.
Non-transition metals Ni, Fe, Mn and transition metal Nb powders are mixed with VC, TiC and TaC. Through ball milling and spark plasma sintering (SPS) technology, Ni/Fe/Mn is used as a binder, and Nb forms carbon vacancy diffusion channels with high-entropy carbides. The mass ratio is controlled to achieve densification and toughening.
High-density, high-hardness, and high-toughness high-entropy carbide ceramic materials were prepared at lower temperatures, solving the problems of high brittleness and sintering difficulties, and improving the overall performance of the materials.
Smart Images

Figure CN122629385A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic composite materials technology, specifically to a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material and its preparation method. Background Technology
[0002] High-entropy ceramics, as a novel class of ultra-high temperature structural materials, have attracted widespread attention in the field of materials science in recent years. High-entropy carbide ceramics, in particular, exhibit excellent high-temperature mechanical properties, extremely high melting points, outstanding wear resistance, and good oxidation and corrosion resistance due to their unique "cocktail effect" and hysteresis diffusion effect. These properties make them highly promising for extreme environment applications such as aerospace thermal protection systems, nuclear energy structural components, high-temperature wear-resistant coatings, and cutting tools. However, the constituent elements of high-entropy carbides are mostly high-melting-point refractory metals with strong covalent bonds and low diffusion coefficients, making the materials extremely difficult to sinter. Furthermore, high-entropy carbide ceramics typically have low fracture toughness and are extremely sensitive to cracks, easily undergoing catastrophic brittle fracture under mechanical impact or thermal shock. This severely limits their reliability and application range as engineering structural materials.
[0003] Currently, one approach is to prepare high-entropy carbide ceramics at relatively low temperatures by adding different component carbides. Chen Lei et al. used metal oxides (Ti, Zr, Nb, Ta, and V / Cr / Mo / W oxides) and reducing carbon powders (carbon black, graphite, or activated carbon) as raw materials, and prepared low-oxygen carbide composite powders using high-energy ball milling and vacuum carbothermal reduction calcination processes. They then synthesized (TiZrNbTaM)C five-component single-phase high-entropy carbide ceramics at high temperatures of 1750-2200 ℃ using hot pressing sintering or spark plasma sintering (SPS). These ceramics exhibited Vickers hardness of 32.3–39.8 GPa, density of 98.5%–99.6%, and fracture toughness of 4.28–4.81 MPa. 1 / 2This study effectively solved the technical challenges of unavoidable oxygen contamination and low density in the preparation of multi-component carbides, resulting in an ultra-hard, highly dense single-phase ceramic material [Chen Lei et al. An ultra-hard five-component transition metal carbide single-phase high-entropy ceramic material and its preparation method: CN110194667B. Harbin Institute of Technology, authorized on September 17, 2021]. Li Mingliang et al. used transition metal carbides TiC, ZrC, HfC, TaC, and VC as raw materials, and prepared (TiZrHfTaV)C five-component high-entropy carbide ceramics at 2000 ℃ / 50 MPa using ball milling wet mixing, rotary evaporation drying, and SPS processes. The optimized molar ratio of Ti:Zr:Hf:Ta:V was 0.25:0.25:0.2:0.2:0.1. This material achieves a single solid solution phase structure with a Vickers hardness of 23.14~33.55 GPa, effectively solving the problems of excessively high sintering temperature and difficulty in densification of traditional high-entropy carbides. Simultaneously, the introduction of cost-effective V element reduces costs and improves high-temperature performance [Li Mingliang et al. A pentagonal high-entropy carbide ceramic and its preparation method: CN120965331A. Zhengzhou University, published November 18, 2025]. Li Lijie et al. used TiC, ZrC, VC, NbC, and Mo2C powders as raw materials, prepared mixed powders by ball milling, and synthesized binary to pentagonal carbide ceramics at 2000-2200℃ using spark plasma sintering. The Vickers hardness reached 17.47~22.38 GPa, and the fracture toughness reached 3.44~5.15 MPa. 1 / 2 By designing a non-equimolar ratio of Nb and V, the fracture toughness of high-entropy ceramics was successfully improved [Li Lijie et al. Compositional Design and Toughening Mechanism of High-Entropy Carbide Ceramics [D]. Zhengzhou: Zhengzhou University, 2023]. Although the above studies have reduced the preparation temperature or improved the fracture toughness of high-entropy ceramics to some extent, the preparation temperature is still as high as 1750~2200 ℃, and the toughness is still at 5.15 MPa. 1 / 2 the following.
[0004] Another approach is to introduce metal binders such as Co and Ni, commonly used in traditional cermets, into high-entropy ceramics. Liu Quanming et al. used at least one non-transition metal (Co, Ni, Fe) and at least four to six transition metal carbides (TiC, WC, Mo2C, TaC, NbC, ZrC, VC, HfC, and Cr2C3) as raw materials. They prepared composite powders via ball milling and synthesized metal-bonded high-entropy ceramics using vacuum or atmospheric pressure sintering at 1400–1500 °C. These ceramics achieved a Vickers hardness of 91.0–92.1 HRA and a fracture toughness of 6.8–9.2 MPa. 1 / 2A high-entropy carbide-based cermet material with both hardness and toughness was obtained [Liu Quanming et al. A preparation method of high-entropy carbide-based cermet: CN119506638B. Jiangxi Mingrui Special Alloy Co., Ltd., authorized on September 2, 2025]. Wang Kuan et al. used transition metals Zr, V, Ta and transition group metal carbides TiC, ZrC, VC, NbC, HfC and TaC as raw materials, and prepared composite powders by ball milling. They then synthesized metal-bonded high-entropy ceramics by SPS method at 1600-2000 ℃, with Vickers hardness reaching 16.1~22.1 GPa and fracture toughness reaching 4.1~8.4 MPa. 1 / 2 Through a non-equimolar ratio design of Z, V, and Ta elements, the solid solution strengthening between transition metals and high-entropy carbides was investigated [Wang Kuan et al. Influence of Transition Metals on the Microstructure and Properties of High-Entropy Carbide Ceramics [D]. Qinhuangdao: Yanshan University, 2024]. Although adding metal binders can lower the sintering temperature and improve toughness, when facing a complex high-entropy carbide matrix, the wettability of a single metal relative to the complex matrix is often poor, the interfacial bonding strength is difficult to control, and it is easy to lead to pore residue or interfacial delamination. Summary of the Invention
[0005] The technical problem to be solved: High-entropy carbide ceramics are prepared at extremely high temperatures and typically have low fracture toughness, making them extremely sensitive to cracks. They are prone to catastrophic brittle fracture under mechanical impact or thermal shock, which severely limits their reliability and application range as engineering structural materials. Traditional cermets typically use Co or Ni as a single binder phase. Although this can improve toughness to some extent, when facing a complex high-entropy carbide matrix, the wettability of a single metal relative to the complex matrix is often poor, making it difficult to control the interfacial bonding strength and easily leading to residual porosity or interfacial delamination. In summary, it is particularly important to develop a novel high-entropy carbide ceramic composite material that can achieve densification at lower temperatures and effectively balance high hardness and high toughness.
[0006] Technical solution:
[0007] A non-transition / transition metal synergistic reinforced and toughened high-entropy carbide ceramic material is prepared from raw materials comprising the following mass proportions: at least one of non-transition metals Ni, Fe, and Mn powder, with a total mass fraction of 8.5-13.6%; transition metal Nb powder, with a mass fraction of 4.3-42.9%; and a mixed powder of VC, TiC, and TaC, with a total mass fraction of 48.3-83.2%.
[0008] Furthermore, the mass fraction of VC powder is 9.6~16.6%, the mass fraction of TiC powder is 9.2~15.8%, and the mass fraction of TaC powder is 29.5~50.8%.
[0009] Furthermore, the raw material also includes Cr3C2 powder, with a mass fraction of 0.01~3%.
[0010] Furthermore, the particle size of Ni, Fe, Mn, Nb, VC, TiC, TaC and Cr3C2 powders is 1~3 μm, and the purity is greater than 99.5%.
[0011] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. The raw material powder with a preset mass fraction is ball-milled using a ball mill, with a ball-to-material mass ratio of 2:1 to 20:1, a rotation speed of 200 to 450 r / min, and the ball milling time is 0.5 to 20 h to obtain a mixed powder. S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The pre-pressed sample is subjected to spark plasma sintering (SPS); the sintering pressure is 40 MPa, the sintering temperature is 1200~1500 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0012] Furthermore, the sintering process and parameters in S3 are as follows: after the graphite mold is fitted with graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa; after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and the vacuuming is stopped after the holding is completed, and argon gas is introduced to -0.05 Pa; then the temperature is increased at a rate of 50~100 ℃ / min to a temperature 50 ℃ lower than the final sintering temperature, and then sintered at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to the final sintering temperature; the temperature is held at the final sintering temperature for 10 min, and the blank is removed after cooling in the furnace.
[0013] 3. Beneficial effects: This invention prepares a high-entropy carbide ceramic with synergistic reinforcement and toughening of non-transition / transition metals by sintering using non-transition and transition metals as binders and high-entropy ceramics as the hard phase via SPS technology. The sintering pressure is 40 MPa, the sintering temperature is 1300~1500 ℃, and the holding time is 10 min. The non-transition metals Ni / Fe / Mn exist as binders to wet the high-entropy carbides, while the transition metal Nb dissolves into the high-entropy carbides to form carbon vacancies, providing a rapid diffusion channel for atomic diffusion during sintering, thus obtaining a high-performance composite material with synergistic reinforcement and toughening of non-transition / transition metals.
[0014] The innovation of this invention lies in introducing non-transition metals Ni / Fe / Mn as tough metal binder phases, and utilizing the solid solution strengthening effect between transition metal Nb and VC, TiC, TaC and Cr3C2 ceramics to construct a high-entropy carbide framework with carbon vacancies. By controlling the mass ratio, the problems of high brittleness and difficult sintering of existing high-entropy ceramics are solved. Attached Figure Description
[0015] Figure 1 The XRD patterns are for Examples 1, 2, 3, 4, 5, 7, and 8.
[0016] Figure 2 The image shows the surface morphology and EDS diagram of Example 1.
[0017] Figure 3 The surface morphology and EDS image are shown in Example 2.
[0018] Figure 4 The surface morphology and EDS image are shown in Example 3.
[0019] Figure 5 The surface morphology and EDS image are shown in Example 4.
[0020] Figure 6 The surface morphology and EDS image are shown in Example 5.
[0021] Figure 7 The surface morphology and EDS image are shown in Example 7.
[0022] Figure 8 The surface morphology and EDS image of Example 8 are shown.
[0023] Figure 9 The stress-strain curves are for Examples 1, 2, 3, 4, 5, 7, and 8.
[0024] Figure 10 The DSC-TG curves are for Examples 1, 2, 3, 4, 5, 7, and 8. Detailed Implementation
[0025] The present invention will now be described in detail with reference to the accompanying drawings.
[0026] As attached Figure 1 To be continued Figure 10 .
[0027] The testing equipment described in this invention are all instruments used in conventional testing methods, such as X-ray diffractometer, Vickers hardness tester (with a load of 5 kgf and a holding pressure of 15 s), apparent porosity and bulk density tester, scanning electron microscope, universal testing machine, and assembled material surface and interface performance tester, etc. Example 1
[0028] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 0.90 g of Ni powder, 4.27 g of Nb powder, 0.96 g of VC powder, 0.92 g of TiC powder, and 2.95 g of TaC powder in an argon glove box and place them in a WC cemented carbide container. Mix them by ball milling for 20 h. The mass of the WC grinding balls is 200 g, and the ball milling speed is 450 r / min.
[0029] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The pre-pressed sample was subjected to spark plasma sintering. The sintering pressure was 40 MPa, the sintering temperature was 1400 ℃, and the holding time was 10 min. Then, the sample was cooled and depressurized to obtain a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material blank.
[0030] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1350 ℃ at a rate of 100 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1400 ℃; the temperature is held at 1400 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0031] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 7.92 g / cm³. 3 ,92.1%,20.2 GPa,5.8 MPa.m 1 / 2 , 1090.3 MPa, 414.0 MPa, 707.9 ℃, 835.0 ℃ and 25.09%. Example 2
[0032] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 0.85 g of Fe powder, 4.29 g of Nb powder, 0.97 g of VC powder, 0.92 g of TiC powder, and 2.97 g of TaC powder in an argon glove box and place them in a WC cemented carbide container. Ball mill the mixture for 20 h. The mass of the WC grinding balls is 200 g, and the ball milling speed is 450 r / min.
[0033] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure is 40 MPa, the sintering temperature is 1500 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0034] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1450 ℃ at a rate of 100 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to 1500 ℃; the temperature is held at 1500 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0035] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 7.68 g / cm³.3 ,90.4%,16.5 GPa,4.9 MPa.m 1 / 2 , 913.8 MPa, 332.6 MPa, 664.9 ℃, 859.6 ℃ and 23.71%. Example 3
[0036] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 0.85 g of Mn powder, 4.29 g of Nb powder, 0.97 g of VC powder, 0.92 g of TiC powder, and 2.97 g of TaC powder in an argon glove box and place them in a WC cemented carbide container. Mix them by ball milling for 20 h. The mass of the WC grinding balls is 200 g, and the ball milling speed is 450 r / min.
[0037] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure is 40 MPa, the sintering temperature is 1500 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0038] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1450 ℃ at a rate of 100 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to 1500 ℃; the temperature is held at 1500 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0039] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 7.75 g / cm³. 3 ,91.2%,17.5 GPa,4.9 MPa.m 1 / 2, 959.6 MPa, 351.6 MPa, 668.1 ℃, 882.6 ℃ and 22.42%. Example 4
[0040] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 1.25 g of Ni powder, 0.43 g of Nb powder, 1.66 g of VC powder, 1.58 g of TiC powder, and 5.08 g of TaC powder in air and place them in a stainless steel container. Mix them by ball milling for 0.5 h. The stainless steel grinding balls weigh 20 g, and the ball milling speed is 200 r / min.
[0041] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure was 40 MPa, the sintering temperature was 1350 ℃, and the holding time was 10 min. Then the temperature was lowered and the pressure was released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0042] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1300 ℃ at a rate of 50 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1350 ℃; the temperature is held at 1350 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0043] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 8.49 g / cm³. 3 ,98.8%,17.9 GPa,5.9 MPa.m 1 / 2 , 660.7 MPa, 255.3 MPa, 789.9 ℃, 970.9 ℃ and 22.01%. Example 5
[0044] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 1.25 g of Ni powder, 0.43 g of Nb powder, 1.66 g of VC powder, 1.58 g of TiC powder, and 5.08 g of TaC powder in air and place them in a stainless steel container. Mix them by ball milling for 0.5 h. The stainless steel grinding balls weigh 100 g, and the ball milling speed is 400 r / min.
[0045] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure was 40 MPa, the sintering temperature was 1350 ℃, and the holding time was 10 min. Then the temperature was lowered and the pressure was released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0046] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1300 ℃ at a rate of 50 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1350 ℃; the temperature is held at 1350 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0047] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 8.50 g / cm³. 3 ,99.0%,20.2 GPa,6.4 MPa.m 1 / 2 , 1839.0 MPa, 750.3 MPa, 829.8 ℃, 911.0 ℃ and 22.38%. Example 6
[0048] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 1.25 g of Ni powder, 0.43 g of Nb powder, 1.66 g of VC powder, 1.58 g of TiC powder, and 5.08 g of TaC powder in air and place them in a stainless steel container. Mix them by ball milling for 1 hour. The stainless steel grinding balls weigh 100 g, and the ball milling speed is 400 r / min.
[0049] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure was 40 MPa, the sintering temperature was 1350 ℃, and the holding time was 10 min. Then the temperature was lowered and the pressure was released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0050] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1300 ℃ at a rate of 50 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1350 ℃; the temperature is held at 1350 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0051] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, and fracture toughness were 8.59 g / cm³. 3 98.8%, 20.1 GPa and 6.3 MPa.m 1 / 2 . Example 7
[0052] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 1.36 g of Ni powder, 0.46 g of Nb powder, 1.04 g of VC powder, 0.99 g of TiC powder, 3.18 g of TaC powder, and 2.97 g of Cr3C2 powder in air and place them in a stainless steel container. Mix them by ball milling for 0.5 h. The stainless steel grinding balls weigh 20 g, and the ball milling speed is 400 r / min.
[0053] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure was 40 MPa, the sintering temperature was 1200 ℃, and the holding time was 10 min. Then the temperature was lowered and the pressure was released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0054] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1150 ℃ at a rate of 50 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1200 ℃; the temperature is held at 1200 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0055] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 7.82 g / cm³. 3 ,98.6%,18.8 GPa,7.7 MPa.m 1 / 2 , 426.5 MPa, 434.1 MPa, 910.5 ℃, 1312.6 ℃ and 23.35%. Example 8
[0056] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 1.36 g of Ni powder, 0.46 g of Nb powder, 1.04 g of VC powder, 0.99 g of TiC powder, 3.18 g of TaC powder, and 2.97 g of Cr3C2 powder in air and place them in a stainless steel container. Mix them by ball milling for 0.5 h. The stainless steel grinding balls weigh 100 g, and the ball milling speed is 400 r / min.
[0057] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure was 40 MPa, the sintering temperature was 1200 ℃, and the holding time was 10 min. Then the temperature was lowered and the pressure was released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0058] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1150 ℃ at a rate of 50 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1200 ℃; the temperature is held at 1200 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0059] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, fracture toughness, compressive strength, flexural strength, initial oxidation temperature, final oxidation temperature, and oxidation weight gain were all 7.83 g / cm³. 3 ,98.7%,17.3 GPa,8.6 MPa.m 1 / 2 , 1666.2 MPa, 859.2 MPa, 1007.8 ℃, 1216.3 ℃ and 22.96%. Example 9
[0060] A method for preparing a non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material includes the following steps: S1. Weighing the powders: Weigh 1.36 g of Ni powder, 0.46 g of Nb powder, 1.04 g of VC powder, 0.99 g of TiC powder, 3.18 g of TaC powder, and 2.97 g of Cr3C2 powder in air and place them in a stainless steel container. Mix them by ball milling for 1 hour. The stainless steel grinding balls weigh 100 g, and the ball milling speed is 400 r / min.
[0061] S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The sintering pressure was 40 MPa, the sintering temperature was 1200 ℃, and the holding time was 10 min. Then the temperature was lowered and the pressure was released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank.
[0062] The specific sintering process and parameters for SPS are as follows: After placing the graphite mold in a graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa. Vacuum is then applied, and after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The specific heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and after the holding period, the vacuum is stopped, and argon gas is introduced to a vacuum degree of -0.05 Pa; then the temperature is increased to 1150 ℃ at a rate of 50 ℃ / min, and then sintered sequentially at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to reach 1200 ℃; the temperature is held at 1200 ℃ for 10 min, and after cooling in the furnace, the blank is removed. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
[0063] After grinding and polishing, the sample underwent microstructure and property testing. The results showed that its bulk density, compactness, Vickers hardness, and fracture toughness were 7.82 g / cm³. 3 98.6%, 16.7 GPa and 8.3 MPa.m 1 / 2 .
[0064] Comparisons of Cases 1, 2, and 3 show that in non-transition / transition metal synergistic reinforcement and toughening of high-entropy carbide ceramics, the addition of Fe / Mn, compared to Ni, reduces the density, hardness, fracture toughness, compressive strength, and flexural strength of the ceramic material. This is because the addition of Fe / Mn inhibits the solid solution and diffusion of Nb and TiC to some extent, reduces the wettability between the metal binder and the high-carbide ceramic, thereby increasing the difficulty of densification and reducing mechanical properties. Although the addition of Fe / Mn lowers the initial oxidation temperature and reduces the initial oxidation resistance, the increase in the termination oxidation temperature and the reduction in oxidation weight gain are beneficial for its use in high-temperature environments. Comparisons of Cases 4, 5, and 6, as well as Cases 7, 8, and 9, show that appropriately increasing the ball-to-powder mass ratio and ball milling speed helps to refine the powder and achieve uniform mixing, thereby significantly improving hardness, fracture toughness, compressive strength, and flexural strength, but it will cause a decrease in oxidation resistance. Furthermore, excessively long ball milling time (Example 6, 1h) can cause performance degradation. A comparison of Cases 5 and 8 shows that although the addition of Cr3C2 reduces hardness and compressive strength, it can effectively reduce sintering temperature and improve the fracture toughness, bending resistance and oxidation resistance of the material.
[0065] Although the present invention has been disclosed above with reference to preferred embodiments, these are not intended to limit the invention. Any person skilled in the art can make various changes or modifications without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention should be defined by the scope of the claims of this application.
Claims
1. A non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material, characterized in that, It is prepared from raw materials comprising the following mass proportions: at least one of non-transition metals Ni, Fe, and Mn powder, with a total mass fraction of 8.5 to 13.6%; transition metal Nb powder, with a mass fraction of 4.3 to 42.9%; and a mixed powder of VC, TiC, and TaC, with a total mass fraction of 48.3 to 83.2%.
2. The non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material according to claim 1, characterized in that, The mass fraction of VC powder is 9.6~16.6%, the mass fraction of TiC powder is 9.2~15.8%, and the mass fraction of TaC powder is 29.5~50.8%.
3. The non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material according to claim 1, characterized in that, The raw materials also include Cr3C2 powder, with a mass fraction of 0.01~3%.
4. The non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material according to claim 3, characterized in that, The particle size of Ni, Fe, Mn, Nb, VC, TiC, TaC and Cr3C2 powders is 1~3 μm, and the purity is greater than 99.5%.
5. The method for preparing the non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material according to any one of claims 1-4, characterized in that, Includes the following steps: S1. The raw material powder with a preset mass fraction is ball-milled using a ball mill, with a ball-to-material mass ratio of 2:1 to 20:1, a rotation speed of 200 to 450 r / min, and the ball milling time is 0.5 to 20 h to obtain a mixed powder. S2. The mixed powder is loaded into a graphite mold for pre-compression at a pressure of 30 MPa for a holding time of 30 s. S3. The pre-pressed sample is subjected to spark plasma sintering (SPS); the sintering pressure is 40 MPa, the sintering temperature is 1200~1500 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material blank. S4. The prepared blank is subjected to surface grinding and deburring to obtain a non-transition / transition metal synergistic reinforcement and toughening high-entropy carbide ceramic material.
6. The method for preparing the non-transition / transition metal synergistically reinforced and toughened high-entropy carbide ceramic material according to claim 5, characterized in that, The sintering process and parameters in S3 are as follows: After the graphite mold is fitted with graphite felt, it is placed in the SPS sintering furnace and the pressure is slowly increased to 40 MPa; after the vacuum in the sintering furnace reaches 60 Pa, sintering is carried out according to the set heating mechanism. The heating mechanism is as follows: the temperature is increased from room temperature to 600 ℃ in 5 min, held at 600 ℃ for 5 min, and the vacuuming is stopped after the holding is completed, and argon gas is introduced to -0.05 Pa; then the temperature is increased at a rate of 50~100 ℃ / min to a temperature 50 ℃ lower than the final sintering temperature, and then sintered at a rate of 15 ℃ / min for 2 min and 10 ℃ / min for 2 min to the final sintering temperature; the temperature is held at the final sintering temperature for 10 min, and the blank is removed after cooling in the furnace.
Citation Information
Patent Citations
A superhard pentagonal transition metal carbide single-phase high-entropy ceramic material and its preparation method
CN110194667B
A method for preparing high-entropy carbide-based cermet
CN119506638B
Five-element high-entropy carbide ceramic and preparation method thereof
CN120965331A
